Indigenous Peoples in Latin America : Economic Opportunities and Social Networks - Patrinos, Harry Anthony (World Bank, Washington, DC, 2012)
Despite significant changes in poverty overall in Latin America, the proportion of indigenous peoples living in poverty did not change much from the early 1990s to the present. While earlier work focused on human development, much less has been done on the distribution and returns to income-generating assets and the effect these have on income generation strategies. The authors show that low income and low assets are mutually reinforcing. For instance, low education levels translate into low income, resulting in poor health and reduced schooling for future generations. Social networks affect the economic opportunities of individuals through two important channels-information and norms. However, the analysis shows that the networks available to indigenous peoples do not facilitate employment in nontraditional sectors.